Pathological changes observed in the finger biopsy of patients with vibration-induced white finger. - Takeuchi, T.; Futatsuka, Makoto; Imanishi, H.; Yamada, Shingo (Scandinavian Journal of Work, Environment & Health, 1986)
Lesion biopsies of 60 fingers from 30 patients with vibration-induced white finger (VWF) and control observations from seven fingers of five referents demonstrated three main characteristic pathological changes. First, in each case, the muscular layers of the arteries revealed intense thickening with strong hypertrophy of individual muscle cells without intimal fibrosis. Periarterial fibrosis was also noted. Arteriosclerosis with foamy cells, lipid deposition, and fibrous sclerosis was occasionally observed. The second main change was demyelinating neuropathy in the peripheral nerves in which a marked loss of nerve fibers had occurred. There was also an increase in the number of Schwann cells and fibroblasts with strong collagen formation. Severe loss of myelin sheath frequently occurred, and relatively smaller axons without myelin which appeared to have regenerated were observed. Perineural fibrosis was also noted. In the third main pathological change connective tissues with collagen were increased not only in the perivascular and perineural lesions, but also abundantly in the corium of the skin. The elastic fibers there had been destroyed. These three principal pathological changes are very useful for the histopathological diagnosis of VWF.